THE IMPLEMENTATION OF TECHNOLOGY-BASED LEARNING EVALUATION TO INCREASE ENGLISH STUDENTS' LEARNING MOTIVATION: CASE STUDY OF E-PORTFOLIO USE - Noor Aida Aflahah; Miftah Al Farhan; Hafizhatu Nadia; Asyifa Asyifa (Intensive Journal, 2023)
This research aims to explore in depth the use of learning evaluation using technology, namely Google Site, which seeks to develop and increase student motivation and creativity in carrying out requested evaluations. This study is an intrinsic case study which was theoretically rooted in a unique case. The case raised in this research was the potential use of e-portfolios as an alternative option in evaluating technology-based learning. This study involved one lecturer and three students as research participants who were selected based on certain criteria or by purposive sampling technique. Lecturers were selected based on their experience in implementing e-portfolios to evaluate learning, and the students were participants in the learning. Research data were collected through semi-structured interviews with open questions, direct observation, and Focus Group Discussion (FGD). The results of this study confirmed the students gave similar opinions stating that e-portfolios could increase their extrinsic and intrinsic motivation. This research only focused on students' opinions regarding the implementation of e-portfolios in increasing their learning motivation. It is hoped that future research can further explore teachers' opinions for more comprehensive results.